(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research studies The Difficulties Encountered by the Barangay Personnel in implementing the Health Protocol during the COVID-19 Pandemic. It is one of the massive problems LGUs and community faces that affect their daily lives. The Philippine National Government, through its Inter-Agency Task Force on Emerging Infectious Disease, outlined various quarantine measures to limit the impact of the COVID-19 pandemic led by the Barangay personnel and other task force agencies. Barangay personnel struggle to cope with this annoying infectious disease, and how they cope with this kind of crisis during their official duties. This study aims to determine and evaluate the impact of the COVID-19 management practices of barangay personnel in implementing health safety measures. The researcher wants to discover and determine the responses of the Barangay personnel to their constituents in society. The descriptive survey method was combined with a phenomenological approach by the researchers. The researcher uses a descriptive survey to study, assess, and delineate the current topic or situation. The purpose of the study is for the researchers to outline a guide to use this method and describe the nature of the real situation at the time of the study. The researchers, the Barangay personnel, and Purok leaders were interviewed. Regardless of the time of their official duties, they gave time for other activities, especially with the visitors. Written survey responses were given to prepare questions for the respondents to answer. Questions were described in tabulated tables to guarantee the validity of the responses and that the respondents correctly understood the specific item in line with the study’s objectives. The study concluded the demographic profile of the two sets of respondents. According to the assessment, the Barangay personnel and Purok leaders of Barangay 177, Caloocan City, had a moderately serious problem during their official duties. On the problems encountered, the outcome was declared serious by the respondents. Meanwhile, Purok Leaders have also revealed problems enforcing health safety standards. Though they have done their best to assist and respond to the crisis, it is not certain that the people will adhere to the basic health standards the local barangays must impose. The respondents strongly agreed upon the proposed measures of the researchers to help the barangay personnel in the implementation of health protocol w The outcomes of the study demonstrate that barangay personnel and purok leaders in Barangay 177, Caloocan City, need enough attention from the government and community in the implementation of the health safety protocols for the preventive actions they will implement to stop the spreading of Infectious disease and also to be prepared in the other potential virus in the future.